IMPLEMENTASI PELIBATAN DAN PEMBERDAYAAN DALAM KUALITAS PADA ORGANISASI PELAJAR MADRASAH ALIYAH SWASTA - Akhmad Ari Wibowo; Achmad Supriyanto; Agus Timan (Tarbawi, 2019)
The purpose of this study was to find out how the implementation of engagement and empowerment in quality at the HDI at MA Muhammadiyah 1 Malang. This study uses a qualitative paradigm with methods of observation, interviews and documents to determine the implementation of engagement and empowerment in quality at the institution. It was found that madrasas implement engagement and empowerment in quality in their student organizations. The implementation process is carried out by establishing a good organizational culture in student organizations through four stages, namely 1) creating a supportive environment, 2) determining targets and overcoming obstacles, 3) implementing and using supporting facilities, 4) assessing, adjusting and improving. In its implementation, trial-error fixes are used so that ongoing evaluations can be carried out. The implementation of engagement and empowerment is felt to have a positive impact on students and on the student's organizational culture. Keywords. Madrasah; Quality; Intra-school students organization; Muhammadiyah Student Association; Engagement and Empowerment